Winter Survivability and Subsequent Performance of Fall-Planted Flax (Linum usitatissimum L.) in Mid-Central Virginia - Alireza Rahemi; Vitalis W. Temu; Maru K. Kering (Agriculture, 2023)
Winter cropping can be used to achieve a double benefit for producers: as soil cover and an additional economic crop cycle. Flax (Linum usitatissimum L.) is a spring crop growing in the northern region of the US and used as a fall cover crop in some southern states. In this study, eight seed-type flax varieties were evaluated for production as a fall/winter crop for the Commonwealth of Virginia, a mid-latitude region. Mixed results were obtained; however, the crop showed winter tolerance and potential productivity, especially when the frequency of sub-zero winter temperatures was low. Planting too early in the fall allows for significant stem development that increases susceptibility to physical damage by snowstorms and winter frost. Seed yield was low compared to spring-planted crops; however, it reached up to 400 kg ha−1 in some varieties. Seed weights were comparable to those found elsewhere for the same or other varieties, and seed protein and crude fat content ranged from 228–270 and 189–234 g kg−1, respectively. Across years and varieties, P, K, Mg, Ca, and S averaged 7.74, 9.88, 3.88, 2.86, and 2.35 g kg−1, respectively. Mineral elements Fe, Zn, Mn, Cu, and B averaged 95, 62, 21, and 10 mg kg−1, respectively. However, early maturity in spring ahead of other grains subjected it to significant losses to wild birds. Fall-planted flax has potential as a cover crop and may be harvested for seed, which in addition to a summer crop, provides a producer with economic returns from two crop cycles per year.